A mechanical and histologic comparative study of the effect of saline, steroid, autologous blood, and platelet-rich plasma on collagenase-induced Achilles tendinopathy in a rat model. Issue 6 (November 2015) - Calandruccio, James H.; Cannon, Tyler A.; Wodowski, Andrew J.; Stephens, Byron F.; Smith, Richard A.
Abstract : Background: To compare the effects of saline, steroid, autologous blood (AB), and platelet-rich plasma (PRP) on the strength and structure of the Achilles tendon in a rat tendinopathy model. Methods: After the use of collagenase to induce an Achilles tendinopathy, 160 Sprague-Dawley rats were divided into four treatment groups (injections with AB, PRP, steroid, and phosphate buffered saline) and an untreated control group. Load-to-failure testing was performed on 85 specimens harvested at 14 days, and histological analysis was done at days 3, 7, and 14 after injection (75 specimens). Results: Tendon strength was found to be decreased in three of the four treatment groups as compared to controls. The AB group appeared to have an increase in strength that approached but did not attain statistical significance. At days 3 and 7, there were no significant histological differences among any of the observational categories, including controls. At day 14, structure of fibers adjacent to the induced tendinopathy site demonstrated significantly more order than control tendons. Discussion: We found no significant difference in tendon strength among treatment groups, although the AB group had the greatest load-to-failure value. The PBS and PRP groups had statistically lower load-to-failure values. Only the structure of the tendon adjacent to the collagenase injection site showed a statistically significant between the AB and the control and saline groups. Clinical Relevance: In this animal model, AB administration may be more effective in improving tendon strength and structure than other injectates used for treatment of tendinopathy. Further studies are needed to evaluate the response, safety, and efficacy of this intervention prior to use on human subjects.